CHANGING TRADITIONS IN INDIAN WRITING IN ENGLISH - Dhandhukiya, Chirag D (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indian English fiction started as a major force with three pillars of Indian English fiction where stories more or less moved around freedom struggle and Gandhian philosophy to country life in India with their traditions, class, caste, religious affairs. But from mere user to English language to major force in style and output was achieved with Indian diasporas contributing to English literature their original tell of living abroad as Indian and their urban stories as well as stories of modern urban Indians. They are well travelled and they can see Indian stories objectively. They are well read and has good idea of Commonwealth literary output. They are writers who are living abroad and they at ease with language and modern in their outlook. These new stories they tell is about youth, urban world, affluent Indians etc. have changed the typical Indian fiction concept. They are the new face of India.